2003
DOI: 10.1093/annonc/mdg285
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase II trial evaluating a three-weekly schedule of irinotecan plus raltitrexed in patients with 5-fluorouracil-refractory advanced colorectal cancer

Abstract: CPT-11 plus raltitrexed is active in patients with 5-FU-refractory ACC, at the expense of moderate toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 26 publications
3
24
1
2
Order By: Relevance
“…The observed pattern of toxicity resembles that described in previous phase I–II trials of the same combination [9,10,11,12,13,14]. Hematological toxicity and mucositis seem to be lower than with combinations of 5-FU and CPT-11, whereas diarrhea, emesis, and asthenia are somewhat higher.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The observed pattern of toxicity resembles that described in previous phase I–II trials of the same combination [9,10,11,12,13,14]. Hematological toxicity and mucositis seem to be lower than with combinations of 5-FU and CPT-11, whereas diarrhea, emesis, and asthenia are somewhat higher.…”
Section: Discussionsupporting
confidence: 80%
“…CPT-11, 350 mg/m 2 was administered as a 60-min infusion followed 1 h later by raltitrexed, 3 mg/m 2 administered as a 15-min infusion, both in a thrice-weekly schedule. This one-day schedule was selected by the consistent phase I data existing and our group’s previous experience [9, 11, 12]. Atropine prophylaxis and antiemetics (dexamethasone plus antiserotoninergic) were routinely prescribed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with these authors, we consider that this administration approach could be more convenient for patients. This same regimen has been used as second-line therapy in a series of 52 patients with 5FU-resistant CRC, where a partial response rate of 13.5% was obtained with moderate toxicity (grade 3 -4 diarrhoea, 23%; grade 3 -4 neutropenia, 17%) (Aparicio et al, 2003). Other authors, however, have investigated the activity and tolerance of CPT-11 administration followed by raltitrexed 24 h later (Stevenson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These polyglutamates are approximately 60-to 100-fold more active than the parent compound and are retained intracellularly [3,4]. In phase III studies in advanced CRC the agent showed similar efficacy to 5-fluorouracil and leucovorin with a less toxicity and a more convenient every three-week schedule [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%